Phenological, developmental, and biomass production responses of malting barley to Azospirillum argentinense inoculation and the role of indole-3-acetic acid - Casal, Enrique; Puente, Mariana Laura; Cassán, Fabricio; López, Gastón; Criado, María Victoria (Sociedad Argentina de Microbiología General (SAMIGE), 2025)
Póster y resumen de ponencia